EFEKTIFITAS PENDEKATAN KETELADANAN DALAM PEMBINAAN AKHLAK SISWA DI MIN BANDAR GADANG - Iswandi, Iswandi (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2019)
The purpose of this reseach is to examine what kind of approach that is given by teachers in fostering the MIN morals of students in Bandar Gadang and find out the constraints and convenience faced by the teacher in building the mor of MIN students in Bandar Gadang. In this paper the authors use field research (Field Research) using qualitative methods to gather information by revealing data and describing events, phenomena that occur in the field as they are. To get the data in this study the authors used techniques, interviews, and observations to teachers at MIN Bandar Gadang. The results of this study illustrate the efforts that have been made by teachers in fostering student morals at MIN Bandar Gadang not only with regard to manners, social procedures, ways of behaving and ways to behave in my daily life. But more deeply, the teacher's example is also seen in the spiritual formation of students through filling their hearts and spirituality with the qualities of patience, responsibility, fairness, honesty, forgiveness and all of these qualities must be reflected in the teacher's personality. The driving factor in fostering student morals is religious understanding students have started to go deep, because the family also provides motivation and encouragement to students and is supported by religious facilities in the school environment, so that the inculcation of moral values to them is easier.